Structural and photophysical characterization of mono- and binuclear Cu(i) complexes based on carbohydrazones: a combined experimental and computational study. Issue 16 (30th March 2016) - Gholivand, Khodayar; Farshadfer, Kaveh; Roe, S. Mark; Gholami, Akram; Esrafili, Mehdi D.
Abstract : The influence of ligand structure and halide variations on the structural and photophysical aspects of complexes was considered, both experimentally and theoretically. Abstract : Pyridinyl carbohydrazone ligands with different positions between functional groups of –NNHC(O)– and Npy ( ortho -, meta - and para -) have been applied for the synthesis of cuprous halide complexes. X-ray crystallography reveals that the ortho analogous ligand, Lo, functions in a chelating mode, adopting a mononuclear structure in complexCo, [CuClLo PPh3 ], while the meta and para analogs, Lm andLp, act as ambidentate ligands, coordinating through the Npy atom in halogen-bridged binuclear complexes [Cu(μ-X)LPPh3 ]2 (X = Cl, Br, I and L =Lm, Lp ). The influence of non-covalent intermolecular interactions on the assembly of the final structures has been discussed by geometrical and Hirshfeld analyses. Moreover, the photophysical properties of the complexes have been explored, both experimentally and theoretically. The influence of ligand structure and halide variations on the structural and photophysical aspects of the complexes has been considered in this study.